Downregulation of PGC-1α Prevents the Beneficial Effect of EET-Heme Oxygenase-1 on Mitochondrial Integrity and Associated Metabolic Function in Obese Mice - Shailendra P. Singh; Lars Bellner; Luca Vanella; Jian Cao; John R. Falck; Attallah Kappas; Nader G. Abraham (Journal of Nutrition and Metabolism)
Background/Objectives. Obesity and metabolic syndrome and associated adiposity are a systemic condition characterized by increased mitochondrial dysfunction, inflammation, and inhibition of antioxidant genes, HO-1, and EETs levels. We postulate that EETs attenuate adiposity by stimulating mitochondrial function and induction of HO-1 via activation of PGC-1α in adipose and hepatic tissue. Methods. Cultured murine adipocytes and mice fed a high fat (HF) diet were used to assess the functional relationship among EETs, PGC-1α, HO-1, and mitochondrial signaling using an EET-agonist (EET-A) and PGC-1α-deficient cells and mice using lentiviral PGC-1α(sh). Results. EET-A is a potent inducer of PGC-1α, HO-1, mitochondrial biogenesis (cytochrome oxidase subunits 1 and 4 and SIRT3), fusion proteins (Mfn 1/2 and OPA1) and fission proteins (DRP1 and FIS1) (p<0.05), fasting glucose, BW, and blood pressure. These beneficial effects were prevented by administration of lenti-PGC-1α(sh). EET-A administration prevented HF diet induced mitochondrial and dysfunction in adipose tissue and restored VO2 effects that were abrogated in PGC-1α-deficient mice. Conclusion. EET is identified as an upstream positive regulator of PGC-1α that leads to increased HO-1, decreased BW and fasting blood glucose and increased insulin receptor phosphorylation, that is, increased insulin sensitivity and mitochondrial integrity, and possible use of EET-agonist for treatment of obesity and metabolic syndrome.